2004
DOI: 10.1303/aez.2004.511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on life history traits of the predatory thrips, Scolothrips takahashii Priesner (Thysanoptera: Thripidae)

Abstract: Scolothrips takahashii is an indigenous thrips in Japan that feeds on many spider mite species. To evaluate whether S. takahashii has potential as a biological control agent for spider mites, we investigated the development, survivorship and life-history parameters of S. takahashii on a diet of Tetranychus urticae (red form) eggs at different temperatures. More than 74% of thrips eggs hatched and more than 76% of newly hatched larvae attained maturity at 15-35°C. No females laid eggs at 37.5 or 40°C. The lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 18 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…Females exhibited Type II responses at various ages tested, and the magnitude of functional response in females aged 3-9 d were significantly greater than 15 d or more. This could be attributed to fact that egg reproduction in females reached a peak at this age at 25°C (Gotoh et al, 2004a). While in males aged 12 d or more, the responses were confirmed to be Type I, their inability to respond to increasing prey density indicated that physiological senescence in males was faster than in females.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Females exhibited Type II responses at various ages tested, and the magnitude of functional response in females aged 3-9 d were significantly greater than 15 d or more. This could be attributed to fact that egg reproduction in females reached a peak at this age at 25°C (Gotoh et al, 2004a). While in males aged 12 d or more, the responses were confirmed to be Type I, their inability to respond to increasing prey density indicated that physiological senescence in males was faster than in females.…”
Section: Discussionmentioning
confidence: 92%
“…Females of S. takahashii were more voracious than males. This, combined with the female-biased sex ratio in population of S. takahashii (Gotoh et al, 2004a), indicates that female may play a more important role in the biological control of phytophagous mites. In this study, we focused mainly on prey eggs consumed by S. takahashii adults, because the egg stage comprises the major proportion of a T. viennensis population (Liu and Wang, 1965;Li et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations